JAVANESE INTERFERENCE IN ENGLISH CONSONANT SPEECH OF THE 5TH PRESIDENT OF INDONESIA - Aziez, Shinta; Arista, Aulia Sandra (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
Having good public speaking is essentially needed for presidents who have a great influence among people. They have to do speeches not only in their native language but also English as the international language. However, Indonesia, which is divergent in its local languages, struggles in eliminating the interference of its dialect when speaking English. This occurred when the 5th president of Indonesia, who is a Javanese lady, made her speech in the state palace which was attended by foreign ministers. This research is aimed at finding out the factors and the interference of Javanese phonemes in the English consonants in the 5th president speech. Descriptive qualitative method is used in this research in which the data were taken from the documentary of the 5th president English speeches. The data were transcribed into phonetic transcription to identify the phonemes pronounced in the speech. The result showed that the interference of Javanese phonemes occurred especially in plosive sounds /b/, /d/, /g/, and /t/, fricative sounds /v/, /Ã°/, /z/, /Êƒ/, and affricate /dÊ’/. The factors influencing the interference are the different phonemes in English and Indonesian, educational and environmental background